Evaluation of stress-strain state of FRP strengthened RC elements in bending. Fracture mechanics approach. (1st February 2020) - Slaitas, Justas; Valivonis, Juozas; Rimkus, Liudvikas
Abstract: The evaluation of stress state of tensile reinforcements is highly important while examining the technical state of concrete structures. Normal cracks in flexural RC elements are the consequence of stress-strain state, on the other hand, the stress-strain state of flexural reinforced concrete structures, strengthened with various types of FRP reinforcements, could be analysed by observing the parameters of normal cracks. Therefore, here proposed method for analysis of such structures relating normal crack parameters to stress-strain state in the element. Not full composite action between concrete and external FRP reinforcement was taken into account by reducing FRP strain through reduction factor based on built-up bars theory. Afterwards, bending moments and mid-span deflections were retrieved using methods of classical mechanics of solids and then numerical results were reliably compared to experimental ones from the tests of RC beams, strengthened with externally bonded CFRP laminates, sheets and near surface mounted GFRP rods, with post-tensioning and initial stress state effects.